Redesigning a Hazardous Waste Storage Facility to Improve Compliance and Safety in a Plastic Packaging Company in Bekasi Regency - Sede, Johanes Surya Utama; Wikaningrum, Temmy (Jurnal Serambi Engineering, 2026)
This study evaluates critical non-compliances in the Temporary Storage Facility for Hazardous and Toxic Waste (TPS LB3) at a plastic packaging manufacturer in West Java, Indonesia. The assessment was conducted in accordance with Government Regulation No. 22 of 2021, Ministry of Environment and Forestry Regulation No. 6 of 2021, and relevant Indonesian National Standards (SNI). A descriptive engineering design approach was applied, integrating gap analysis, qualitative risk assessment using a 5×5 risk matrix, and Computer-Aided Design (AutoCAD 2024). Key deficiencies identified include insufficient spill containment capacity (0.015 m³ vs. 0.22 m³), improper drainage of emergency eyewash to stormwater systems, inadequate aisle width (10 cm vs. 60 cm standard), and unsafe co-storage of incompatible waste types. The proposed redesign (10.5 m × 6.06 m) addresses these issues through an 8-meter drainage system, a 0.225 m³ containment basin, ANSI Z358.1-compliant eyewash installation, improved layout with proper spacing and zoning, and verified ventilation and lighting systems. The redesigned facility is capable of safely accommodating a peak waste accumulation of 4.566 tons within a 90-day storage period while meeting regulatory compliance.